Combined Simulation and Mutation Studies to Elucidate Selectivity of Unsubstituted Amphetamine‐like Cathinones at the Dopamine Transporter. Issue 5 (8th November 2016) - Seddik, Amir; Geerke, Daan P.; Stockner, Thomas; Holy, Marion; Kudlacek, Oliver; Cozzi, Nicholas V.; Ruoho, Arnold E.; Sitte, Harald H.; Ecker, Gerhard F.
Abstract: The dopamine and serotonin transporter proteins (DAT, SERT) play a vital role in behavior and mental illness. Although their substrate transport has been studied extensively, the molecular basis of their selectivity is not completely understood yet. In this study, we exploit molecular dynamics simulations combined with mutagenesis studies to shed light on the driving factors for DAT‐over‐SERT selectivity of a set of cathinones. Results indicate that these compounds can adopt two binding modes of which one is more favorable. In addition, free energy calculations indicated the substrate binding site (S1) as the primary recognition site for these ligands. By simulating DAT with SERT‐like mutations, we hypothesize unsubstituted cathinones to bind more favorably to DAT, due to a Val152 offering more space, as compared to the bulkier Ile172 in SERT. This was supported by uptake inhibition measurements, which showed an increase in activity in SERT‐I172V. Abstract :